Transparansi Informasi Pelayanan Surat Izin Usaha Pada Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kabupaten Bantaeng - Azis, Irsan; Fatmawati, Fatmawati; Mone, Ansyari (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study aimed to determine the form of transparency of information on Business License services at the Investment and One Stop Integrated Services Office in Bantaeng Regency. This study used a qualitative method. The number of informants in this study was 10 people.  data collection were observation, interview, and documentation. The results of this study showed that from the aspect of the availability and accessibility of documents from the process of providing information on technical requirements and procedures for business licensing regarding business license services in the department had been running well, aspects of clarity and completeness of information could provide comfort in providing information when serving the community and timely in providing information on business licensing procedures if they had entered their working hours, the aspect of the openness of the process was not be  well, this could be seen from the non-publication of all business licensing procedures that should be a benchmark of user assessment, and aspects of the regulatory framework that were ensure transparency was well publicized and could be understood by service users.Keywords: Information Transparency, Business License Services